2022
DOI: 10.1155/2022/4543078
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Aromatherapy as a Natural Complementary and Alternative Therapy in Cardiovascular Disease: A Comprehensive Systematic Review

Abstract: Background. The purpose of this study was a comprehensive review of studies on the effect of aromatherapy with plant essential oils on the improvement of some conditions, for example, anxiety, stress, sleep quality, fatigue, and pain in people with cardiovascular disease. Materials and Methods. We carried out this systematic review based on the instructions of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Ethical agreement was not necessary as main data have not been collected. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Odors have shown the property of increasing memory recall, inducing relaxation, or even enhancing humans’ mental abilities. Aromatherapy is a discipline that has been used for millennia as an alternative medicine in different cultures, resulting in effective treatment of some disorders such as insomnia [ 1 ], anxiety [ 2 ], and depression [ 3 ]. In addition to these clinical applications, the effects of fragrances on the human mind and behavior is also of great interest for all those applications related to everyday life, such as cosmetics, personal care, nutrition, comfort, and psychophysical well-being [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Odors have shown the property of increasing memory recall, inducing relaxation, or even enhancing humans’ mental abilities. Aromatherapy is a discipline that has been used for millennia as an alternative medicine in different cultures, resulting in effective treatment of some disorders such as insomnia [ 1 ], anxiety [ 2 ], and depression [ 3 ]. In addition to these clinical applications, the effects of fragrances on the human mind and behavior is also of great interest for all those applications related to everyday life, such as cosmetics, personal care, nutrition, comfort, and psychophysical well-being [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, aromatherapy increases positive emotions [21] and decreases negative emotions [17][18][19]22] . Furthermore, these effects have been reported in systematic reviews of cardiovascular disease [23] . However, most studies examining the effects of aromatherapy have been conducted at rest; nevertheless studies conducted during exercise are scarce.…”
Section: Introductionmentioning
confidence: 81%
“…Lavender has beneficial effects on sleep, both direct and indirect. The indirect effect may be related to other properties of lavender, as previous studies have shown the effectiveness of lavender to reduce cancer complications (MARDANI et al, 2022), in women who are in the menopause period (ROOZBEH et al, 2018) in cardiovascular diseases (ALMOHAMMED et al, 2022), pain relief (BAGHERI-NESAMI et al, 2014).…”
Section: Data Presentation and Analysismentioning
confidence: 99%